The application of Kohonen and Multilayer Perceptron Networks in the speech nonfluency analysis - Szczurowska, Izabela; Kuniszyk-Jóźkowiak, W.; Smołka, E. (Archives of Acoustics, 2006)
Paper reports the neural network tests on ability of recognition and categorising the nonfluent and fluent utterance records. 40 of 4-second fragments containing the blockade before words starting with stop consonants (p, b, t, d, k and g) and including from 1 to 11 stop consonant repetitions and 40 recordings of the speech of the fluent speakers containing the same fragments were applied. Two various networks were examined. The first, Self Organizing Map (Kohonen network), with 21 inputs and 25 neurons in output layer, was used to reduce the dimension describing the input signals. As a result of the analysis we achieved vectors consisting of the neurons winning in a particular time point. Those vectors were taken as an input for the next network that was Multilayer Perceptron. Its various types: with one and two hidden layers, different kinds and time of learning were examined.